2019
DOI: 10.1097/ijg.0000000000001296
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea in Patients With Primary-open Angle Glaucoma: No Role for a Screening Program

Abstract: Précis: In this study, we found a high prevalence of obstructive sleep apnea (OSA) among patients with primary open-angle glaucoma (POAG) but this was not different (nor was OSA more severe) to matched people without glaucoma. Rationale: It has been proposed that OSA might be a contributing factor in the development of POAG and by extension that there could be a role for screening people with POAG for OSA. Objectives: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Measures of OSA severity in this subset of participants also did not differ from the rest of the cohort. Likewise, Wozniak et al's recent case-control study 33 of over 300 middle-aged and older adults found similar rates of OSA in patients with open-angle glaucoma and controls (58% vs 54%). Findings from other large cohort [14][15][16] and casecontrol investigations 16,34 also do not support an association between the two conditions.…”
Section: Discussionmentioning
confidence: 84%
“…Measures of OSA severity in this subset of participants also did not differ from the rest of the cohort. Likewise, Wozniak et al's recent case-control study 33 of over 300 middle-aged and older adults found similar rates of OSA in patients with open-angle glaucoma and controls (58% vs 54%). Findings from other large cohort [14][15][16] and casecontrol investigations 16,34 also do not support an association between the two conditions.…”
Section: Discussionmentioning
confidence: 84%
“…This female predominance was also found by Balbay et al in Turkey [29] and Onen et al in France [30], 54.3% and 57.1% respectively. On the other hand, there is a male predominance in the study conducted by Wozniak et al [31]. Our results could be justified by the fact that women are more numerically represented and more health conscious hence their high participation in the study.…”
Section: Discussionmentioning
confidence: 43%
“…Studies have shown that OSAHS is more frequent in glaucoma patients than in the control group. Indeed, Wozniak et al [31] reported that among patients with moderate and severe forms of OSAHS, glaucoma patients accounted for 22% compared to 16% among controls. It can also be noted that the high risk of OSAHS is prevalent in glaucoma patients compared to the low risk.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 All other studies included were comparative and included multiple groups. 11 , 16 22 For these studies, data on OSA from the glaucoma group were extracted for quantitative analysis. For studies with more than one glaucoma group, both groups were combined before data extraction.…”
Section: R Esultsmentioning
confidence: 99%
“…For studies with more than one glaucoma group, both groups were combined before data extraction. Both studies by Wozniak et al were grouped as one so that only data from Wozniak et al was extracted being that it provided an updated data set to the study by Wozniak et al 16 , 21…”
Section: R Esultsmentioning
confidence: 99%